Monetary vs Fiscal Policy, Which is More Effective? Case Studies of Asean-5 Countries (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
This study purpose to analyze the effectiveness of monetary and fiscal policies on economic growth in ASEAN-5 (Indonesia, Malaysia, Philippines, Thailand, and Vietnam) from 1998 to 2019. Monetary policy is measured from inflation, fiscal policy is measured from government spending, and economic growth is measured from GDP’s growth based on constant prices 2010. Data analysis techniques use Vector Auto Regressive (VAR), Impulse Response Function (IRF), and Variance Decomposition (VD). The results show that monetary policy is much more effective than fiscal policy in Asean-5.